What is the role of the government? (A dialectical-relational approach to discursive struggle in the arena of community education presented by an Indonesian online media) - Ruswan Dallyono (Passage: Journal of English Language and Literature, 2023)
The Indonesian national law states that the National Education System could be universally implemented in a complete and totally integrated manner. There are three key words to ponder: universal, complete, and integrated. As a replacement, a complement, and/or a supplement to formal education, community education ideally should have had an appropriate system and management. The present study aims to reveal issues in the implementation of community education in Indonesia as represented on an online media and to examine the solutions to those problems. The existence of such problems under investigation makes the values of the National Education System, namely universality, completeness, and integration appear to be impracticable. Under the framework of a qualitative method, this study used a Critical Discourse Analysis (CDA) of Fairclough’s tradition (1997). The selected texts from an online media, called the Jakarta Post, were analysed by following the method and stages of dialectical-relational approach (Fairclough, 2013). The analysis was not only leaned on textual analysis, but also covered an inter-discursive analysis. This study reveals that there is a ‘social wrong’, namely the overwhelming level of responsibility possessed by community education. Generally, the problems of community education can be solved through the collaboration of various elements in the society. The Central Government, specifically, the Ministry of Education, should deal with and implement feasible programs starting from solving the philosophical issues: the different concepts of educating and teaching, being adaptive (able to deal with the current issues to be placed in pedagogical practices), and a fair distribution of funding (expenses for providing infrastructure). This form of contemplation can be considered to be a part of an essential discourse analysis to comprehend the dialectics of semiotic elements and textual evidence. Moreover, this study also shows that there are still many actual problems in the Indonesian education sector.